Editorial: Special Edition on Banking, Competition & Corporate Law: Confronting Contemporary Challenges of Banking, Competition & Corporate Law to Enhance Consumer Protection - Chitimira, Howard (Potchefstroom Electronic Law Journal, 2024)
Although Zimbabwe has established several institutions to combat money laundering and related crimes, there is a perception that inadequate measures are taken to apprehend offenders responsible for financial crimes. Institutions such as the Financial Intelligence Unit (FIU), the Zimbabwe Anti-Corruption Commission (ZACC), the Zimbabwe Republic Police (ZRP), the National Prosecuting Authority (NPA) and the Reserve Bank of Zimbabwe (RBZ) have done little to prove that the government of Zimbabwe is resolute in combatting money laundering. On the contrary, it increasingly appears that these institutions are poorly equipped and lack the necessary capacity to enforce and uphold anti-money laundering (AML) measures in Zimbabwe. Further, there appears to be a selective application of the law, with one set of rules for individuals or institutions that are perceived as political adversaries of the incumbent establishment and a different set of rules for the political elite. Consequently, the selective application of the law projects Zimbabwe as a jurisdiction that is somehow tolerant to money laundering, corruption and related financial crimes, thereby lowering and tarnishing the standing of the country in the global economic community of nations. This paper provides a regulatory analysis of the AML role-players in Zimbabwe in order to assess their functions in combatting financial crimes. It also analyses whether these role-players are effective and substantively executing their responsibilities therein. The authors argue that while Zimbabwe is well able to effectively combat money laundering through the even application of the law to all persons regardless of their political or economic standing, it is imperative that its AML institutions operate without fear, favour or prejudice. This is crucial in combatting money laundering and instilling confidence in the general public's perception of AML institutions in Zimbabwe.
Keywords: Banking; Competition; Financial crimes; Financial markets; Securities

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

A comparative appraisal of creditor protection mechanisms under South African company law - Sibanda, Mandhlaenkosi (University of South Africa, 2024)
The study comparatively scrutinised creditor protection mechanisms entrenched in South African Corporate law to determine their effectiveness in advancing creditor interests in company affairs. The enquiry was triggered by the need for corporate laws to adapt to and align with the pace of global economic changes in open and democratic societies. The 2004 DTI Policy document on South African Corporate Law Reform (SACLR) proposed a shift from the traditional shareholder-centric view, which espouses shareholder importance in corporate governance, to a model that retains the supremacy of shareholder interests while simultaneously catering to the interests of other stakeholders (the enlightened shareholder value approach). In light of the DTI policy proposal, the parliament, in enacting the South African Companies Act 71 of 2008 (the Companies Act), reflected on the need to provide appropriate redress to investors' and third parties (creditors`) rights in the preamble to this piece of legislation. It was based on the forgoing expositions that this research work sought to establish whether the South African Corporate law had been adequately modelled to protect creditors and to look beyond the traditional company’s goal of profit maximisation for the shareholder at the expense of other stakeholders, such as the creditors, who equally have stakes in the success and continuation of the company. Thus, a comparative doctrinal and critical analysis of creditor protection laws from selected cognate jurisdictions was undertaken to determine the efficacy of the protection mechanisms accorded to creditors under the South African corporate jurisprudence. It is thus the researcher's findings that the South African provisions on mechanisms to protect creditors are set in motion and are, therefore, effective to a greater extent, subject to legislature dealing with some discrepancies as per lessons drawn from comparator jurisdictions and recommendations. Conclusively, the Companies Act should clearly include the creditor’s interests in those of the company and thus give a secondary duty to directors to ensure creditor interests, among other non-member stakeholders, are assertively safeguarded.
Keywords: Company controllers; Company law; Corporate entity; Corporate law; Corporate veil; Credit systems; Creditor interests; Creditor protection mechanisms; Creditors; Directors; Employees; Investors; Shareholders; Stakeholder constituencies; Stakeholder interests; Stakeholders; Third parties

Internationalisation patterns of African sharing economy companies: The role of gateway markets - Ochieng, Irene Achieng; Thornton, Heidi Coral; Owusu, Richard Afriyie (Journal of Business Research, 2024)
Sharing economy companies (sharecoms) have been internationalising rapidly, including entering African markets. Little research has been conducted on the strategies and behaviours of African sharecoms. Questions have been raised as to whether existing theories adequately explain the internationalisation of African firms. Thus, we analyse the internationalisation patterns of six African sharecoms, focusing on time, speed, and scope. The findings indicate that firms apply unique combinations of various internationalisation models. A novel pattern of internationalisation where the firms use “foreign gateway markets” as strategic “launchpads” before rapidly internationalising was also uncovered. Locational advantages, strategic networks, and relative technological advancement characterise the foreign gateway markets. We also propose the concept of “complex regional context” to define the context of emerging regions with many neighbouring countries with the potential for high levels of internationalisation but low levels of international business due to the lack of common enabling frameworks and institutions.
Keywords: Emerging African markets; Foreign gateway markets; Internationalisation; Patterns; Sharing economy